The Effectiveness of the Jigsaw Strategy on Improving Self-Efficacy in Mathematics among Tenth-Grade Students (The International Journal of Educational Sciences and Arts, 2024)
The study aimed to reveal the effectiveness of the Jigsaw strategy in improving the self-efficacy of tenth-grade female students. To achieve the aim of the study, the study used the quasi-experimental approach, and the researchers prepared a self-efficacy scale, in addition to ensuring its validity and reliability. The quasi-experimental approach was used with a pre-post measurement. (40) female students from Hawara Secondary School for Girls in the city of Irbid participated in the study. The sample was selected using the available method and was distributed equally into the experimental and control study groups. The study concluded that there are statistically significant differences at the significance level (α = 0.05) between the performance averages of female students in the experimental and control groups on the self-efficacy scale in favor of the experimental group. Based on the results of the study, the study recommended the necessity of directing mathematics teachers towards employing the Jigsaw strategy in teaching mathematics, and training them on how to apply it in teaching instead of traditional methods.
Keywords: Jigsaw Strategy; Self-Efficacy; Tenth Grade